The runaway jury - Grisham, John. (London : Arrow Books, 2010)
The Big Four in the tobacco industry think they have all their bases covered in an upcoming trial in which a widow is suing for the smoking-related death of her husband, but they did not count on an inside operator who has a personal grudge and a sure-fire plan to bring them down.
Adult.
Adult
Keywords: Trials -- Fiction; Trials -- Fiction; Biloxi (Miss.) -- Fiction; Biloxi (Miss.) -- Fiction; Legal stories